Pengaruh pengetahuan, sanksi, dan kualitas pelayanan pajak terhadap wajib pajak kendaraan bermotor di kabupaten agam - Fadhilah Al Usna; Dedy Djefris; Dita Maretha Rissi (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2022)
This study aims to determine whether tax knowledge, tax sanctions, and tax service quality are related to taxpayer compliance. This type of research is quantitative research. The data collection method in this study used oral questionnaires to respondents as well as interviews, observations, and literature studies. The population of this research is all Agam Regency Taxpayers who are registered in SAMSAT Lubuk Basung. The sample used in this study were taxpayers who were registered at SAMSAT Lubuk Basung, amounting to 100 people. The sampling technique used is the purposive sampling technique used in determining the criteria from those tested in this study. Data analysis in this study used multiple linear regression analysis using the SPSS version 25 program. The results of this study indicate that knowledge of taxation, taxation and service quality have a significant effect on taxpayer compliance in paying for motorized vehicles in Agam Regency. Keywords: Knowledge of taxation, tax sanctions, service quality, and tax compliance